Supercritical fluid extraction, micro-encapsulation and application of betacyanin-extract from red pitaya (Hylocereus polyrhizus (WEBER) Briton & Rose) - Fathordoobady, Farahnaz (2015)
There is a progressive demand for natural pigments in colouring food stuff instead of synthetic colourants because of human health concern. Red pitaya (Hylocereus polyrhizus) is found to be a promising source of more stable natural red pigment of betacyanins, with a deep purple colour compared to red beet, commercial source of betacyanins pigment, and is also regarded as a rich source of antioxidants. Due to the undesirable properties of betacyanins from beet root and adverse environmental effects of solvent extraction which is mostly used for betacyanins recovery, the aim of present study was to investigate an appropriate method for obtaining betacyanins from Hylocereus polyrhizus and increasing the heat and storage stability of pigment extract from the fruit peel, a waste product of juice processing which would be considered as a natural red pigment with bioactive properties. In this regard supercritical fluid extraction (SFE) with CO2 as solvent and EtOH/water mixture as co-solvent was used for the extraction of betacyanins. Pressure and temperature of process as the most significant parameters affecting extraction condition as well as co-solvent percentage which improves the extraction of polar bioactive materials, were chosen as supercritical fluid extraction variables. It was found that SFE method had betacyanins recovery of 86.7-92.5% compared to solvent extraction. A 23 factorial design was used for optimization of SFE method and investigation the effects of extraction parameters (temperature, pressure and co-solvent concentration) on response variables of yield (%), total betacyanins content (mg/100 ml), colour properties (a*) and antioxidant activity (IC50) of extracts. The linear effects of pressure, temperature and co-solvent concentration were found to be significant on all the response variables (p<0.05). Optimal SFE conditions were identified as 30 MPa pressure, 40oC temperature, and 20% co-solvent for the flesh, and 25 MPa pressure, 50oC temperature, and 15% co-solvent for the peel. The response variables at optimal point were assessed as maximum extraction yield of 3.93% and 10.90 %, total betacyanins content of 25.67 mg/100 ml and 98.65 mg/100 ml, redness (a*) of 59.29 and 57.51, and IC50 of 1.2 mg/ ml and 2.1 mg/ ml for the peel and flesh, respectively. Experimental values for response variables at these optimal conditions matched well with the predicted values. The pigment profile of the peel and flesh extracts from solvent and SFE methods was detected using HPLC and ESI- LC/MS/MS technique. Betanin, phyllocactin and their C- 15 respective isoforms were the major betacyanins constituents detected in all of the samples of extracts. In this study, hylocrenin and its C-15 isoform which were previously identified in Hylocereus genus were detected in trace amounts. In order to improve the stability of betacyanins extract of the peel of Hylocereus polyrhizus obtained through the optimal condition of SFE, a good source of betacyanins pigment with potent antioxidant activity, ionization gelation method of micro-encapsulation with alginate as wall material was used. Based on the equation derived from RSM-face centered composite design of experiment, the combination of 2.9% alginate (%), 161.9 mM CaCl2 (mM) and 26.4% betacyanins extract (v/v) was identified as the optimal mico-encapsulation condition for high efficiency, minimum mean particle size and the best matrix uniformity of microencapsulated extract. To assess the potential of micro-capsules as an antioxidant carrier, the release behavior of alginate-loaded betacyanins extract in simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) was also investigated. The results of heat stability and storage study showed significant improvement (p<0.05) of half-life, and total betacyanins and antioxidant activity retention in micro-encapsulated betacyanins extract in comparison with non-capsulated extract and commercial betanin solution (control). Further study on the application of micro-encapsulated betacyanins extract in two food systems (yoghurt drink and jelly) revealed that during storage at 4°C for 60 days, the retention of total betacyanins content and antioxidant activity in two food products with betacyanins micro-capsules was significantly higher (p<0.05) than in products colourd with non-capsulated betacyanins and betanin solution. Sensory attributes evaluation of prepared yoghurt drinks and jelly samples coloured with betacyanins micro-capsules represented significant higher overall acceptability (p<0.05) compared to two other samples. Moreover, the products containing betacyanins extract micro-capsules had faced lower colour changes (ΔE*) compared to products coloured with non-capsulated betacyanins and commercial betanin (control) during storage condition. These findings revealed that betacyanins micro-capsules from the peel of Hylocereus polyrhizus is an alternative natural red pigment with high potential of antioxidant activity and desired stability, and can be exploited for some food formulation.